The use of two languages in Samuel Beckett's art - Beer, A (1988)
﻿ This study argues that Samuel Beckett's works in English and French reveal the organising energy of a "bilingual consciousness". Bilingualism is no personal eccentricity but the foundation for Beckett's mature art, without which it could not have developed. He has never been a unilingual writer; at every stage of his career his two languages have enriched, challenged and opposed each other. Bilingual art has allowed Beckett to move between linguistic circles, claiming as his own a transitional space that has protected his need for imaginative solitude. Gradually abandoning the cultural specificity of his early works in favour of archetypal settings that "translate" successfully to other contexts, he has focussed directly on what unites rather than divides human communities. Yet his writing retains an evident alertness to, and love of, the linguistic and cultural resources of English and French. His alternations between languages and his frequent activities as translator and self- translator contribute to a detachment from generic conventions that encourages innovation. Thus the often-criticised marginality of the bilingual has become for Beckett a source of strength. This analysis draws on a close reading of certain key texts, crossing languages freely to follow Beckett's own development. The prose has central place, because it spans his entire career, and because his most radical innovations have occurred in prose to be, subsequently, transferred in new forms to the drama. Chapter I presents Beckett's dual language-use in a wider context, exploring the early exposure afcd later suppression of "bilingual awareness, the implications of bilingualism for his artistic outlook, and the bilingual aesthetic he has developed. The remaining chapters draw on a new chronology of his writing and translating activities to show the development of his dual language-use and how it has interacted distinctively at each period with his artistic goals and practice.